Element-specific amorphization of vacancy-ordered GeSbTe for ternary-state phase change memory. (1st September 2017) - Wang, Xue-Peng; Li, Xian-Bin; Chen, Nian-Ke; Chen, Qi-Dai; Han, Xiao-Dong; Zhang, Shengbai; Sun, Hong-Bo
Abstract: GeSbTe alloys have the ability of rapidly transforming between amorphous and crystalline phases. Therefore, they can be used in the non-volatile phase change memory. Recently, a vacancy-ordered cubic Ge2 Sb2 Te5 ( VOC GST) phase change material where the vacancies are highly ordered in the (111) plane, has been experimentally demonstrated by STEM. However, studies are mainly on the structural characterization, rather than on the phase change behavior and possible applications of the VOC GST. Here, using first-principles molecular dynamic simulations, we study the melt-quenched amorphization process and its possible applications. We find that the VOC GST exhibits a quasi-two-dimensional amorphization process that is triggered by the diffusion of Ge atoms but not others. A partial amorphous ( P-amor ) phase is obtained, which can act as an intermediate state between the pure amorphous and pure crystalline phases for possible ternary-state data storage. Graphical abstract: